2
$\begingroup$

i have posted this question on MO, and they referred me to post here . one starts with the formal definition of zeta :

$$\displaystyle \zeta (s)=\prod_{p}\frac{1}{1-p^{-s}} $$

then : $ \ln(\zeta (s))= -\sum_{p}\ln(1-p^{-s})=\sum_{p}\sum_{n=1}^{\infty}\frac{p^{-sn}}{n}$

using the trick : $\displaystyle p^{-sn}=s\int_{p^{n}}^{\infty}x^{-s-1}dx $

then :

$$ \frac{\ln\zeta (s)}{s} = \sum_{p}\sum_{n=1}^{\infty}\int_{p^{n}}^{\infty}x^{-s-1}dx$$

up until now, things make perfect sense , but the following line is mysterious to me :

$$ \frac{\ln\zeta(s)}{s}=\int_{0}^{\infty}f(x)x^{-s-1}dx $$

where $f(x) $ is the weighted-prime counting function . how is this formula derived !?!?

$\endgroup$
  • 1
    $\begingroup$ If I remember right you simply write $\sum_p$ as $\sum_n (\pi(n)-\pi(n-1))$. Note that the Bracket is $1$ when n prime and 0 otherwise. Now, the difference becomes a difference of two series, the second one being indexed one step lower, reindex it , combine and done. $\endgroup$ – N. S. Feb 14 '12 at 13:08
  • $\begingroup$ Can you define the weighted prime counting function? Is it: $f(x)=\sum_{p<x} \lfloor \log_p x\rfloor$? $\endgroup$ – Thomas Andrews Feb 14 '12 at 13:37
  • $\begingroup$ thanks for the reply, but i am afraid i am not following the logic . the sum over $\pi(n)-\pi(n-1)$ is quite clear . but the integral part is what puzzles me. could you show the work step by step please . $\endgroup$ – Mohammad Al Jamal Feb 14 '12 at 13:42
  • $\begingroup$ $ f(x) = \sum_{n=1}^{\infty} \frac{\pi(x^{1/n})}{n} $ it's also called the riemann prime counting function .mathworld.wolfram.com/RiemannPrimeCountingFunction.html $\endgroup$ – Mohammad Al Jamal Feb 14 '12 at 13:44
  • $\begingroup$ It becomes a little more obvious if you realize your formula after the formula form $p^{-sn}$ is wrong - it is missing a factor of $\frac{1}{n}$. It should be: $$\frac{\ln\zeta (s)}{s} = \sum_{p}\sum_{n=1}^{\infty}\frac{1}{n}\int_{p^{n}}^{\infty}x^{-s-1}dx$$ $\endgroup$ – Thomas Andrews Feb 14 '12 at 14:00
7
$\begingroup$

Note, per my comment above, you left out a $\frac{1}{n}$ in the formula for $\frac{\log\zeta(s)}{s}$. It should have been:

$$\frac{\ln\zeta (s)}{s} = \sum_{p}\sum_{n=1}^{\infty}\frac{1}{n}\int_{p^{n}}^{\infty}x^{-s-1}dx$$

Re-arrange the sum as: $$\frac{\log{\zeta(s)}}{s}=\sum_{n=1}^\infty \frac{1}{n}\sum_p \int_{p^n}^\infty x^{-s-1}dx$$ Now, in general, for any function $g$: $$\sum_p \int_{p^n}^\infty g(x) dx = \int_0^\infty \pi(x^{1/n})g(x)dx$$

I'll leave that step to to you. So we get:

$$\frac{\log{\zeta(s)}}{s}=\sum_{n=1}^\infty \frac{1}{n}\int_0^{\infty} \pi(x^{1/n})x^{-s-1}dx = \int_0^\infty f(x) x^{-s-1}dx$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.